Parenting Styles and Its Impact on Emerging Adults in Nepal - Bhattrai, Namrata (NPRC Journal of Multidisciplinary Research, 2024)
This study investigates gender variations in parenting practices and how they affect the resilience of emerging adults in Nepal. Using a quantitative, cross-sectional methodology, data were obtained from 565 participants aged 18-28 from Kathmandu colleges using proportional stratified random sampling. To ensure clarity, standardized measures such as the Parenting Inventory II, Adult Wellbeing Assessment, and Brief Resilience Scale were administered online in both Nepali and English from January to May 2023. The data suggest that responsive parenting and autonomy-granting greatly contribute to resilience, whereas demandingness has no noticeable impact. Gender differences were minimal, with males expressing somewhat more autonomy than females. These results emphasize the importance of responsive and autonomy-supportive parenting practices in fostering resilience among emerging adults.